MEMBANGUN KARAKTER KEBANGSAAN MELALUI PENDIDIKAN MULTIKULTURAL BERBASIS AL-QURAN - Akmal Rizki Gunawan Hsb; Siti Asiah (Attadib: Journal of Elementary Education, 2018)
One of the problems the community posmodern is the euphoria of celebrating differences. However, when the author of saving the current multiculturalism it reached eksremitasnya, it will give birth to racism. I.e. the peak when an individual or group to establish the difference so as not to be reunited. Surely this discourse is very contrary to the explanation of the Koran (al-Hujarat: 13), which indicates that the entire nation is comrade, the whole man is a friend, and most recently the goal is peace. Although the reality was, to this day Islam often desebut as a religion of violence and anti-kemajemukan. Thus, how the concept of national character building through multicultural education based al-Quran?. Approach libraries research towards literature-related literature, this study concludes that the concept of multicultural education based Koran in building national character brings the humanist theory of teosentris includes five principles, namely: Believe In The One Supreme God, Humanity, Unity, Democracy, Justice. It is based on the description of al-Quran regarding interconnection and harmonious interaction between man and God, man with himself, man with human. The methods used in this study is the tafsir method maudhu'i and the historical-critical method-contextual. While the approach used was qualitative and quantitative approach. A qualitative approach is used to generate data which is the descriptive results are presented in the form of qualitative. Whereas the quantitative approach, is used to generate the data through a series of observations about the verses that relate.